2018
DOI: 10.4172/neuropsychiatry.1000340
|View full text |Cite
|
Sign up to set email alerts
|

The Neural Basis of Self-Touch in a Pain-Free Situation

Abstract: Objective:Self-touch is thought to be an act of coping with harmful or stressful situations, based on the mechanism which suppresses somatosensory perception as well as somatosensory cortex activity, and sympathetic activity. In addition, this suppression can be observed in even nonpainful and non-stressful situations. However, its detailed neural mechanism remains unknown. Several studied have shown, not only that the descending pain modulatory system (DPMS) plays critical roles in painful situations, but als… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 65 publications
0
9
2
Order By: Relevance
“…Previous brain-imaging studies on self–other distinction in the tactile domain are inconsistent, reporting weaker activation (16), deactivation (18), and even stronger activation during self-produced tactile stimulation (23). However, these early studies are constrained by small sample sizes ( n = 8–12).…”
mentioning
confidence: 95%
See 1 more Smart Citation
“…Previous brain-imaging studies on self–other distinction in the tactile domain are inconsistent, reporting weaker activation (16), deactivation (18), and even stronger activation during self-produced tactile stimulation (23). However, these early studies are constrained by small sample sizes ( n = 8–12).…”
mentioning
confidence: 95%
“…A consequence of this cancellation is the observation that people cannot tickle themselves (15). The suggested mechanism for this phenomenon is an attenuation of cortical sensory processing (1618). Such attenuation has been found for auditory and visual processing (1921).…”
mentioning
confidence: 99%
“…Thus, whether similar neural mechanisms are activated with mild tactile stimulation such as affiliative and gentle touch remains unconfirmed. A recent fMRI study has shown that there is intrinsic functional connectivity in the DPMS in non-painful situations [46], and another one has shown that self-touch activates the DPMS in a pain-free and stress-free situation [47]. These studies may support the possibility that the DPMS regulates somatosensory afferents based on their emotive valence, even for mild somatosensory stimuli with subtly different movement patterns.…”
Section: Introductionmentioning
confidence: 83%
“…Moreover, the DPMS can function even in the absence of painful/stressful stimulation, because intrinsic functional connectivity among DPMS regions (including the ACC and RVM) has been demonstrated in such situations [46]. Moreover, the DPMS is activated during self-touching behaviors in pain-free and stress-free situations [47].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation